Akro gymnastic / Merrylove Glory Albert - Albert, Merrylove Glory (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Performance in most sports is determined by the athlete’s technical, tactical, physiological and psychological/social characteristics. The physical aspect will be evaluated with a focus on what limits the performance, and how training can be conducted to improve performance. This project aims to provide a better exposure to local community, specifically on the artistic gymnast, whereby it is accessible to those who have zero experience to the sport. The main objective of this project is to normalize the practice that high-performance sport does not necessarily have to happen in elite league nor it must use high-tech equipment. The concept is transformable design through manipulation as module in a curvilinear manner immitating the gymnast movement.